Antecedents of consumer brand engagement and brand loyalty. Issue 5 (23rd March 2016) - Leckie, Civilai; Nyadzayo, Munyaradzi W.; Johnson, Lester W.
ABSTRACT: Literature on consumer engagement is growing significantly, yet there is limited empirical research on its drivers and outcomes. This study examines the key drivers and outcomes of consumer brand engagement (CBE) in the context of Australian mobile phone service providers. The results reveal that consumer involvement, consumer participation and self-expressive brand have differing effects on the CBE dimensions (cognitive processing, affection and activation) and brand loyalty. Specifically, involvement, participation and self-expressive brand are all found to positively impact cognitive processing. Also, involvement and self-expressive brand positively influence affection. While, a positive relationship is established between involvement and activation, self-expressive brand emerges as a negative driver of activation. Further, the results show that affection and activation positively influence brand loyalty. Surprisingly, cognitive processing negatively impacts brand loyalty, whilst involvement (unlike participation and self-expressive brand) has a positive direct effect on brand loyalty. Managerial and academic implications, as well as areas for future research are discussed.